OPTIMASI WAKTU INKUBASI VAKSIN H5N1 PADA TELUR AYAM BEREMBRIO DENGAN SUHU 37OC TERHADAP TITER HEMAGLUTINASI - Fuji Lestary, Rizka; Kurniati, Iis; Dermawan, Asep; Riyani, Ani (Politeknik Kesehatan Kemenkes Bandung, 2024)
Avian Influenza virus subtype H5N1 can infect animals as well as humans due to its high pathogenicity. Avian Influenza virus contains hemagglutinin protein that can agglutinate red blood cells. The purpose of this study was to determine the optimal incubation time, namely 3 days, 4 days, and 5 days and whether there are differences in the different incubation times. The type of research used was descriptive. The samples used were Avian Influenza Vaccine subtype H5N1 inoculated into embryonated chicken eggs aged 9-11 days. The allantois fluid produced from vaccine inoculation in embryonated chicken eggs can be tested for hemagglutination to determine its titer. The results showed that the optimum incubation time was 3 days and the optimum hemagglutination titer at the 3rd day incubation time was 1/256, at the 4th day incubation time was 1/256, and at the 5th day incubation time was 1/512. The data were analyzed using One-Way Anova test on SPSS. In conclusion, there was a significant difference in hemagglutination titer in the H5N1 vaccine inoculated in embryonated chicken eggs for 3 days and 4 days against the incubation time for 5 days.